CLASSIFICATION OF ADVERTISING AND ITS PRACTICAL SIGNIFICANCE IN INCREASING EFFICIENCY OF THE MANAGEMENT OF CONSUMERS BEHAVIOR - DYBCHUK, LIUDMYLA; HOLOVCHUK, YULIIA; PCHELIANSKA, GALYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the context of economic transformation, there has been great interest in the problems of managing consumer behavior through advertising. The article considers the essence of advertising in terms of development of social and economic space, which is aimed at improving the sphere of business and information activities, as well as the protection of social values. The classification of advertising by target audience, coverage area, means of transmission, functions and goals is proposed, as these criteria allow to some extent to cover and outline the impact of advertising on society as a whole, its sphere of activity and each of its representatives individually. There are eight basic types of advertising, each of which has its own specifics and can be used depending on the goals of the business structure. It is noted that the effective factors that have proven their effectiveness in the system of means of influencing consumer behavior are advertising. The authors pay special attention to the fact that a significant advantage and information resource of the enterprise is effective advertising. It is also noted that the main engine of sales today is the Internet, namely - advertising on the Internet (a form of impersonal presentation of information about goods or services on the Internet). The purposes and types of Internet advertising are described. It is determined that the advertising campaign is one of the tools of the strategic plan of the enterprise, as a result of which the use of advertising in the management of all activities of the enterprise is an important and integral part of the enterprise management system as a whole. Methods and ways of planning an advertising campaign are described. It is noted that the effectiveness of advertising or advertising campaign in general is characterized by the ratio of results (effect) of a particular advertising campaign and the cost of its implementation. Criteria for the effectiveness of advertising will be considered its objectivity and specificity, truthfulness and ethics, the availability of the necessary information, the correctness of the evidence presented in favor of the object, as well as the direction of the addressee.